Foliar spraying with zinc nanoestrutures in cucumber seddlings (Cucumis sativus) - Quirino-García, Arelis; Martínez-Alonso, Claudia; Sabino-López, Juan Elías; Espinosa-Rodríguez, Mariana; Vázquez-Villamar, Mirna; Maldonado-Peralta, María de los Ángeles (Ecosistemas y Recursos Agropecuarios, 2025)
The foliar spraying effect of zinc nanostructures (ZnO-NE) was studied on cucumber seedlings growth in greenhouse. The treatments were four solutions made thought nanostructures with Zn (ZnO-BE) obtained by professional (MP) and domestic (MD) microwaves, and by direct precipitation (PD); the positive control (TP) was commercial fertilizer (ZnSO4) and negative (TN) water. Cucumber seeds were immersed for 2 h in the solution with the respective Zn2+ (30 mg L-1) source and sowed in polystyrene containers with peat and perlite (1:1 v/v), in greenhouse. Seedlings with two true leaves were sprayed with the corresponding solutions, every seven days for three weeks. Lower seedling height was presented in TN and greater stem diameter with ZnO-NE of MD. The ZnO-NE from MD and PD produced wider leaves (6.98 and 6.89 mm), PD longer leaves (6.01 mm); Seedlings treated with ZnO-NE of MP and MD increased leaf area (360.86 and 313.82 cm-2). The three ZnO-NE sources increased root length, and root volume stood out in TP (10.2 mL). Fresh root biomass was higher with ZnO-NE from MD (3.54 g). All Zn sources improved the fresh and dry weight of stem; fresh (6.5 g) and dry (0.85 g) weight of leaf highlighted with ZnO-NE from PD. Foliar spraying with ZnO-NE is an alternative to improve growth and biomass production on cucumber seedlings grown in greenhouse.